Determination of the efficacy of post exposure anti rabies vacine therapy in Sri Lanka - Wimalaratne, O.V (My University, 1994)
Twenty five patients who received post exposure anti rabies cell culture vaccine at the general hospital colombo were randomly selected for this study.Result obtained in this study after statistical analysis showed that all vaccinees not only had 100 per cent sero conversion but also had protective antibody levels= 0.5 IU/ml against rabies.Therefore ,the 2:1:1 schedule used for post exposure anti rabies vaccine therapy in government hospitals of sri lanka has been proved to evoke adequate protective antibody levels against rabies.